Spectrum of false positivity for the fourth generation human immunodeficiency virus diagnostic tests. Issue 1 (December 2016) - Liu, Peter; Jackson, Patrick; Shaw, Nathan; Heysell, Scott
Abstract Novel fourth generation screening and confirmatory human immunodeficiency virus (HIV) assays are now commercially available and incorporated into new diagnostic algorithms. We report two cases involving a total of three patients which highlight the spectrum of false positivity for both the Abbott Architect p24 antigen/antibody assay and the confirmatory Multispot antibody differentiation test. We then discuss the mechanisms for false positivity and the associated clinical conditions or laboratory scenarios that may predispose to inaccurate interpretation.